From “Government to Governance”? A Systematic Literature Review of Research for Urban Green Infrastructure Management in Latin America - Breen, Anya; Giannotti, Emanuel; Flores Molina, Muriel; Vásquez, Alexis (Frontiers in Sustainable Cities, 2020)
The concept of Urban Green Infrastructure (UGI) has emerged in response to the need to highlight and ensure access to the multifunctional benefits of green spaces in changing cityscapes. Recent literature reviews around UGI have focused on environmental benefits and services, and the management of these spaces has been comparatively neglected. In addition to this, the core conceptual and practical research around UGI management has been produced in the Global North, and far less research has been generated in Latin America, despite the contextual challenges and opportunities brought by this rapidly urbanizing and diverse region. In response, this trilingual systematic review asks: What are the research trends in terms of topics, and case studies that characterize UGI management research in Latin America? Which management types are the focuses of this research? A total of 47 publications, found through Scopus, Web of Science and SciELO, were subjected to both quantitative and qualitative assessment. The research was both geographically concentrated and predominantly recent. Government-led initiatives made up the highest proportion of the research, and more than half of the publications described local government as the principle actor in the management of the UGI studied. Community-run initiatives were consistent across the temporal span of the articles found, and their established presence was supported by the qualitative review. Findings also revealed a directional push towards governance practices, but significant obstacles in the form of: weak local government; divisions driven by a lack of context-sensitive approaches to informal settlements and socioeconomic segregation, and a management discourse that jarred with urban practices by indigenous communities. Through demonstrating the contribution of existing literature on UGI management in Latin America, this review highlights the need for further published research on the region.